Implementation of the activity approach for the development of engineering students’ creative potential - Titova, O. A. (Problems of Engineer-Pedagogical Education, 2019)
The task of engineering education is to train a competent engineer capable of innovative activity under the conditions of globalization and automation of production processes. That requires the development of students’ engineering creativity. The results of the present research reveal that modern learning technologies are scarcely used and that reproductive types of students’ learning and cognitive activity dominate while studying at university. The research is aimed at determining the peculiarities of the implementation of the activity approach to the organization of the educational process. An activity is a conscious, purposeful process which is determined by a certain sequence of actions and operations. It has an information basis, purpose, list of criteria and a certain decision-making algorithm based on these criteria. The article presents the features of the engineering activity which should be perfectly known by the future expert. The features refer to the process of searching for an engineering solution to the problem: identifying and analyzing the problem, searching for or inventing a possible solution, modeling a potential solution, prototype manufacturing and testing, improving the original solution, planning and managing the process, preparing technical documentation. The implementation of the activity approach creates conditions for the development of the creative potential of the engineer through his/her phased involvement in educational and cognitive activities, organized with the use of effective pedagogical technologies and aimed at the implementation of the above-mentioned features of engineering activities.